Acanthoic acid, unique potential pimaradiene diterpene isolated from Acanthopanax koreanum Nakai (Araliaceae): A review on its pharmacology, molecular mechanism, and structural modification. (August 2022) - Dou, Jia-Yi; Jiang, Yu-Chen; Cui, Zhen-Yu; Lian, Li-Hua; Nan, Ji-Xing; Wu, Yan-Ling
Abstract: Acanthoic acid (AA) is a pimaradiene diterpene isolated from the root bark of Acanthopanax koreanum Nakai (Araliaceae) with a wide range of pharmacological activities, including anti-cancer, anti-inflammatory, anti-diabetes, liver protection, gastrointestinal protection, and cardiovascular protection. In addition, AA promotes its pharmacological effects by targeting liver X receptors (LXRs), nuclear factor-kappa B (NF-κB), Toll-Like Receptor 4 (TLR4) and IL-1 receptor-associated kinase (IRAK) signaling pathways, or AMP-activated protein kinase (AMPK) signaling pathway, etc. Also, some studies focus on the structural modification of AA to improve its pharmacological activities. The review summarizes the pharmacological activities, molecular mechanism, and the structural modification of AA, which might supply information for the development of AA in the future. Graphical abstract: Image 1 Highlights: Acanthoic Acid is active ingredient from Acanthopanax koreanum Nakai (Araliaceae). A Review on the pharmacology, molecular mechanism, and structural modification of AA. Provide experimental and theoretical basis for the research of AA and its derivatives. Benefit for the development of new drugs based on Acanthoic acid.